Improving Advance Care Planning for Hospitalized Patients With Heart Failure - Tobin Mathew; Akash Patel; Kyle DiGrande; Nathalie De Michelis; Behram Mody; Dawn Lombardo (Palliative Medicine Reports, 2023)
Advance care planning (ACP) is a valuable and proven approach for enhancing end-of-life communication and quality of life for individuals with heart failure (HF) and their family members. However, the adoption of ACP in practice is still lower than desired. According to University of California, Irvine Medical Center HF metrics, only 15.3% of hospitalized HF patients had completed ACP documentation before discharge, as recorded in the electronic medical record (EMR). This quality improvement project aimed to investigate whether the rate of ACP completion could be increased by utilizing EMR reminders to health care teams regarding individual patients. Personalized reminders were sent to providers for each hospitalized patient diagnosed with HF, who did not have existing ACP documentation in the EMR, to encourage completion of ACP documentation. Our findings have shown that, during the three-month intervention period, the average ACP completion rate was 21.0%. This represents a 5.7% absolute increase in ACP completion compared to the six months before our intervention (15.3%); a relative increase of 37.3%. Direct message reminders to providers prove to be an effective method for enhancing ACP completion among this specific patient group.